(untitled) (Swiss Medical Weekly, 2024)
BACKGROUND: Maintaining physical activity throughout life is crucial for overall health and wellbeing. Yet the age-related decline in average physical activity, a natural phenomenon also observed in animals, poses a challenge. This study aimed to investigate whether participation in organised sports supported by the Swiss Youth+Sports (Y+S) programme is associated with sustaining or enhancing physical activity among children and adolescents during 5 years of follow-up. METHODS: The longitudinal study was nested in the population-based SOPHYA (Swiss children’s Objectively measured PHYsical Activity) cohort. Participants aged 6–16 years at SOPHYA1 (2014) with complete accelerometer data from baseline and follow-up assessment (SOPHYA2, 2019) were included. The primary exposure was participation in organised sport during the follow-up period, calculated by linkage with the Y+S database as the number of days with at least one activity in Y+S-offered programmes for ages 5 to 20 years. The primary outcome was the categorisation of participants into physical activity “improvers” or “worseners”. Improvers in the respective physical activity categories – total activity counts per minute (CPM), minutes in moderate-to-vigorous activity (MVPA), minutes in light activity (LPA) and minutes in sedentary behaviour (SB) – increased or maintained their active physical activity during the 5 follow-up years. Information on confounders and effect modifiers (sex, age, body mass index (BMI), language region, household income, education) was obtained by self-report at baseline. Logistic regressions examined the relationship between organised sport participation and the probability of being a physical activity improver in each physical activity intensity category separately. Covariates for the final models were selected through a stepwise procedure based on the Bayesian information criterion from a maximal model containing all covariates as well as all two-way interactions with organised sport and between them. All models were a priori adjusted for technical variables (season of measurement; wear time; duration of follow-up). RESULTS: The analysis included 432 participants. There was a strong CPM, MVPA and LPA decline from 2014 to 2019, but an increase in SB. Nevertheless, the prevalence of improvers was 22.5% for CPM, 9.5% for MVPA, 26.9% for LPA and 9.7% for SB. Engagement in organised sport between 2014 and 2019 was positively associated with CPM, MVPA and SB, but not with LPA improver status. For 30 additional days of participation in organised sport over the five years of the study, the odds of being an improver vs being a worsener increased by 4.0% for CPM (95% CI: 0.13–7.69), 6.2% for MVPA (95% CI: 0.82–11.54) and 6.0% for SB (95% CI:−1.49–13.97). CONCLUSION: The results provide supporting evidence that organised sport in the context of the Swiss Y+S programme may empower the young to maintain an active lifestyle and even offset the age-related decline in physical activity.